Wear-resistant self-cleaning PE film and preparation method thereof

By adding ZrO2/FSi-SiO2@OMMT wear-resistant self-cleaning agent to the polyethylene film, the problems of vacuuming and wear of the polyethylene film are solved, and significant improvements in wear and self-cleaning performance are achieved, and mechanical and heat resistance are improved.

CN119684705AActive Publication Date: 2025-03-25FUZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510036209.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-25
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

Polyethylene films are prone to adsorbing dust and wear severely during use, and lack wear resistance and self-cleaning properties.

Method used

By adding ZrO2/FSi-SiO2@OMMT as wear-resistant self-cleaning agent, nanosilicon dioxide and medium-sized zirconium dioxide are loaded onto the modified montmorillonite to form a multi-scale ultramicrostructure filler to increase the roughness and dispersion of the composite material.

Benefits of technology

The wear resistance and self-cleaning properties of polyethylene films are significantly improved, and their dispersion and compatibility in the matrix resin are enhanced, while the heat resistance and mechanical properties are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684705A_ABST
    Figure CN119684705A_ABST
Patent Text Reader

Abstract

The invention discloses a wear-resistant self-cleaning polyethylene film and a preparation method thereof. The wear-resistant self-cleaning polyethylene film is prepared from the following raw materials in parts by weight: 90 parts of LLDPE (Linear Low Density Polyethylene), 2-5 parts of a wear-resistant self-cleaning agent ZrO2 / FSi-SiO2 coated OMMT, 0.5-1 part of an antioxidant 1010, 0.5-1 part of an antioxidant DLTP and 1-3 parts of polyethylene wax. The wear-resistant self-cleaning PE film is prepared by the following steps: putting the components into a stirrer, uniformly mixing, drying, carrying out extrusion granulation, carrying out extrusion casting, carrying out mirror surface opposite pressing, cooling, trimming, pressurizing and rolling to obtain the wear-resistant self-cleaning PE film. According to the wear-resistant self-cleaning agent disclosed by the invention, the organically modified OMMT is used as a carrier, the hydrophobically modified SiO2 is firstly loaded and then combined with the ZrO2, and the obtained wear-resistant self-cleaning agent has excellent wear resistance and good self-cleaning performance. Meanwhile, ZrO2 / FSi-SiO2 (at) OMMT is used as a rigid medium with excellent performance, so that the mechanical property of the composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer composite material processing, and particularly relates to a wear-resistant self-cleaning PE film and a preparation method thereof. Background Art

[0002] Polyethylene (PE) is a thermoplastic resin obtained by polymerization of ethylene. Its output accounts for about 1 / 4 of the total plastics, and the proportion of films is close to 50%. PE is widely used in life, such as the production of films, daily necessities, various hollow containers of various sizes for industrial use, pipes, calendering tapes and ligatures for packaging, ropes, fishing nets and weaving fibers, wires and cables, etc. The extensive application of polyethylene is not only due to its excellent chemical properties, such as excellent low temperature resistance and acid and alkali corrosion resistance; but also its mechanical properties are relatively good, with high toughness and strength, can withstand strong tensile and compressive forces, high impact strength, and good impact resistance. With the development of modern society, polyethylene film has been widely used in daily life due to its heat resistance, cold resistance, and moisture retention. In order to meet people's needs in life, functional polyethylene film has received widespread attention. However, in actual application, the outer surface of polyethylene film is prone to adsorb a large amount of dust, which is due to various small molecule additives, as well as the influence of light and heat aging; at the same time, the wear of polyethylene film during use is also relatively serious. Therefore, there is an urgent need to develop a polyethylene film with wear-resistant and self-cleaning properties.

[0003] Silicon dioxide is a non-toxic and non-polluting particle with stable chemical properties, good thermal stability and weather resistance, while nano silicon dioxide has a high specific surface area and good dispersibility. It is precisely because of these unique properties that nano silicon dioxide has a wide range of applications. Zirconium dioxide has a certain function of absorbing ultraviolet rays, and has excellent chemical stability, thermal stability, non-toxicity and other properties. Zirconium dioxide with a smaller particle size has greater activity and good dispersibility, which determines that zirconium dioxide is a widely used inorganic raw material with excellent application prospects.

[0004] Montmorillonite (MMT) is composed of nanometer-thick silicate sheets with negative charges on the surface, which are stacked together by the electrostatic interaction between the layers. The unit cell in its crystal structure is composed of two layers of silicon-oxygen tetrahedrons sandwiched between a layer of aluminum-oxygen octahedrons, forming a unique one-dimensional layered nanostructure. As a natural and inexpensive material, MMT may be a good choice for constructing micrometer-level roughness due to its micrometer-level layered structure. In addition, montmorillonite has strong adsorption capacity and cation exchange properties. This is because there are a large number of exchangeable cations and water molecules between its layers, which makes its interlayer domain have the characteristics of interlayer exchange and interlayer adsorption. Therefore, in order to improve the performance of montmorillonite, it is usually subjected to inorganic or organic modification. Organic modification changes the surface polarity and interlayer spacing of montmorillonite by adding organic modifiers, thereby enhancing its dispersibility and compatibility in the polymer matrix. Summary of the invention

[0005] The purpose of the present invention is to provide a wear-resistant self-cleaning PE film and a preparation method thereof. The present invention has a scientific and reasonable formula, a simple and practical process flow, and by adding a wear-resistant self-cleaning agent, the produced PE film has excellent wear resistance and self-cleaning properties.

[0006] To achieve the above object, the present invention adopts the following technical solution: The present invention provides a wear-resistant self-cleaning polyethylene film, wherein the polyethylene film comprises the following raw materials by weight: LLDPE 90 parts; 2-5 parts of wear-resistant self-cleaning agent; Antioxidant 1010 0.5-1 part; 1-3 parts of polyethylene wax; Antioxidant DLTP 0.5-1 part; The wear-resistant self-cleaning agent is ZrO2 / FSi-SiO2@OMMT.

[0007] The preparation method of the wear-resistant self-cleaning agent ZrO2 / FSi-SiO2@OMMT comprises the following steps: (1) Preparation of OMMT: 3 g of micron-sized montmorillonite was added to 120 mL of deionized water, stirred at room temperature for 30 minutes, 0.1 mol / L NaOH solution was added to adjust the pH of the solution to 12, and stirring was continued at 80 °C for 3 hours; 1.9 g of hexadecyltrimethylammonium bromide was dissolved in 50 mL of deionized water and added to the above solution and stirring was continued for 3 hours. After the reaction was completed, the mixture was centrifuged, washed, and dried. back Get OMMT; (2) Preparation of FSi-SiO2: First, add 5 mL of tetraethyl orthosilicate to a mixed solution of ethanol and ammonia water, and let it stand for 3 h to obtain SiO2 sol; add 0.37 g of KH-570 to the SiO2 sol, stir evenly at 60 °C for 2 h, centrifuge after the reaction is completed, and dry to obtain FSi-SiO2; (3) Preparation of ZrO2 / FSi-SiO2@OMMT: Add 2.30 g FSi-SiO2 and 1.50 g ZrO2 into 20 mL deionized water, adjust the pH of the solution to 3 with hydrochloric acid, and stir at 60 °C for 30 min. Then add 2.50 g perfluorooctyltriethoxysilane and 7.50 g OMMT, and reflux at 60 °C for 13 h. After the reaction, the resulting solution was dried at 50 °C and then ground and sieved to obtain powdered ZrO2 / FSi-SiO2@OMMT.

[0008] Furthermore, in step (2), the volume ratio of ethanol to aqueous ammonia is 10:1.

[0009] The present invention also provides a method for preparing the wear-resistant self-cleaning polyethylene film, which is characterized by comprising the following steps: (1) After the wear-resistant self-cleaning agent, antioxidant 1010, antioxidant DLTP and polyethylene wax are mixed evenly, they are added into a high-speed mixer and mixed evenly with LLDPE particles, and then dried at 60°C for 1 hour; (2) Adding the dried material into a twin-screw extruder and obtaining masterbatch by extrusion granulation; (3) The obtained masterbatch is dried and then added to a casting machine for extrusion casting, mirror pressing, cooling, trimming, and pressurized winding to obtain a wear-resistant self-cleaning PE film.

[0010] Furthermore, the speed of the high-speed stirrer in step (1) is 300 r / min and the temperature is 60°C.

[0011] Furthermore, the extrusion temperature of the twin-screw extruder used in step (2) is: 150°C in the first section, 170°C in the second section, 165°C in the third section, 160°C in the fourth section, 155°C in the fifth section, and 150°C in the sixth section; the screw speed is 10 r / min.

[0012] Furthermore, the casting process used in step (3) is direct casting, the casting roller is a chrome-plated steel roller, the thickness of the chrome-plated layer is 0.01 to 0.015 mm, the diameter of the steel roller is 500 mm, and the middle height of the steel roller is 0.20 to 0.25 mm; the temperature of the steel roller is set to 35 to 40°C; the pressurized winding process is pressurized winding on a 60-65A liquid silicone rubber roller, and the pressurized pressure is 5 to 8 kgf.

[0013] The present invention uses OMMT obtained by modifying montmorillonite with a high surface area as a carrier, loads nano-sized SiO2 onto OMMT, and then interacts with ZrO2 to obtain ZrO2 / FSi-SiO2@OMMT with good wear-resistant and self-cleaning properties. Nano-sized SiO2 is modified by a silane coupling agent to obtain FSi-SiO2 with excellent wear resistance and hydrophobicity, which is loaded onto OMMT and then combined with ZrO2. In this process, PFOTES is added to modify the three materials to be wear-resistant and hydrophobic, and the surface energy of the materials is also reduced. The OMMT obtained by organically modifying the micron-sized MMT with hexadecyltrimethylammonium bromide (CTAB) and grafting PFOTES not only provides micron-scale roughness for the wear-resistant self-cleaning agent, but also improves its dispersibility and compatibility in PE resin, thereby greatly improving the wear-resistant and self-cleaning properties of the PE film.

[0014] The beneficial effects of the present invention are: (1) The present invention obtains a wear-resistant self-cleaning filler having multiple nano- and micro-scale ultrastructures by loading small-sized (10-100nm) nano-silicon dioxide and medium-sized (500-1000nm) zirconium dioxide onto organically modified micron-sized MMT. The three materials of different scales work synergistically to increase the roughness of the composite material and improve the wear resistance and self-cleaning performance of the material.

[0015] (2) The nanoparticles used in the present invention originally have good dispersibility and thermal stability. After being organically modified, the dispersibility and compatibility of the filler in the matrix resin are further improved, which not only greatly improves the wear resistance and self-cleaning properties of the composite material, but also improves the heat resistance and mechanical properties of the composite material. The micron-sized MMT is modified with CTAB to obtain OMMT, and PFOTES is grafted onto the surface of OMMT, which greatly improves its hydrophobicity and compatibility with the matrix material.

[0016] (3) The present invention combines nanomaterials of various sizes to obtain an antibacterial and antifouling filler that is not only low-cost and has superior performance, but is also non-toxic and pollution-free and very environmentally friendly. Therefore, it has excellent application prospects and a wider range of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the Fourier infrared image of the wear-resistant self-cleaning agent ZrO2 / FSi-SiO2@OMMT.

[0018] Figure 2 This is a scanning electron microscope image of OMMT obtained after organic modification and grafting of the micron-sized MMT in Example 1.

[0019] Figure 3This is a scanning electron microscope image of FSi-SiO2 prepared in Example 1 of the present invention.

[0020] Figure 4 This is a scanning electron microscope image of ZrO2 / FSi-SiO2@OMMT prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with specific embodiments to make the present invention easier to understand, but the present invention is not limited to these embodiments.

[0022] Example 1 The preparation method of the wear-resistant self-cleaning PE film comprises the following steps: 1. Specific preparation process of wear-resistant self-cleaning agent ZrO2 / FSi-SiO2@OMMT: (1) 3 g of micron-sized (1-10 μm) montmorillonite (MMT) was added to 120 mL of deionized water and stirred at room temperature for 30 minutes. NaOH solution (0.1 mol / L) was added to adjust the pH of the solution to 12. The mixture was stirred in a water bath at 80 °C for 3 hours under magnetic stirring. 1.9 g of hexadecyltrimethylammonium bromide (CTAB) was dissolved in 50 mL of deionized water and added. The mixture was stirred for 3 hours. The final product was centrifuged and washed three times with deionized water and ethanol. After drying at 60 °C for 12 hours, OMMT was obtained.

[0023] (2) First, 5 mL of tetraethyl orthosilicate (TEOS) was added to a mixed solution of ethanol (50 mL) and ammonia water (5 mL, concentration of 28%) and allowed to stand for 3 h to prepare SiO2 sol. Then, 0.37 g of KH-570 was added to the SiO2 sol and stirred evenly at 60°C for 2 h. The product was centrifuged several times and collected to obtain the modified SiO2 particles. After drying in a drying oven at 50°C for 10 h, FSi-SiO2 with a particle size of 10-100 nm was obtained.

[0024] (3) Add 2.30 g FSi-SiO2 and 1.50 g ZrO2 (500-1000 nm) into a three-necked flask containing 20 mL deionized water, adjust the pH to 3 with hydrochloric acid, and stir at 60 °C for 30 min. Then add 2.50 g PFOTES (perfluorooctyltriethoxysilane) and 7.50 g OMMT, and reflux at 60 °C for 13 h. Finally, the mixed solution was dried in an oven at 50 °C and then ground and sieved to obtain powdered ZrO2 / FSi-SiO2@OMMT.

[0025] 2. Mix 2 parts by weight of ZrO2 / FSi-SiO2@OMMT, 0.5 parts by weight of antioxidant 1010, 0.5 parts by weight of antioxidant DLTP, and 1 part by weight of polyethylene wax, and then mix them evenly with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, and then place them in a 60°C oven to dry for 1 hour.

[0026] 3. Add the dried raw materials into a twin-screw extruder. The temperature of the first section of the twin-screw extruder is 150°C, the temperature of the second section is 170°C, the temperature of the third section is 165°C, the temperature of the fourth section is 160°C, the temperature of the fifth section is 155°C, and the temperature of the sixth section is 150°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0027] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and then added to the casting machine for extrusion casting, mirror pressing, cooling, trimming, and pressurized winding to obtain a wear-resistant self-cleaning PE film. The casting process is direct casting, the casting roller is a chrome-plated steel roller, the chrome-plated layer thickness is 0.01 mm, the steel roller diameter is 500 mm, and the middle height of the steel roller is 0.20 mm; the steel roller temperature is set to 40°C; the pressurized winding process is pressurized winding on a 60 A liquid silicone rubber roller, and the pressurized pressure is 7Kgf.

[0028] Figure 1 Fourier transform infrared image of ZrO2 / FSi-SiO2@OMMT at 2925cm -1 There is a -CH3 stretching vibration peak at 2854cm -1 There is a -CH2 stretching vibration peak at 1470cm -1 There is a -CH2 bending vibration peak at 1060cm -1 There is an asymmetric stretching vibration absorption peak of Si-O-Si at 800cm -1 There are Si-O-Si symmetric stretching vibration absorption peaks at 449cm -1 There is a Si-O-Si bending vibration absorption peak at 654cm, indicating that the organic modification of MMT has successfully grafted CTAB and PFOTES on its surface to obtain OMMT; it also indicates that FSi-SiO2 is successfully loaded on OMMT. -1 The presence of characteristic peaks of Zr-O indicates that ZrO2 is successfully combined with FSi-SiO2@OMMT to obtain the wear-resistant self-cleaning agent ZrO2 / FSi-SiO2@OMMT.

[0029] Figure 2This is a scanning electron microscope image of OMMT obtained after organic modification and grafting of the micron-sized MMT in Example 1. It can be seen that the surface of OMMT is a lamellar structure, the surface is smooth and clear, the layers are stacked on each other, and the lamellar structure is dispersed.

[0030] Figure 3 This is a scanning electron microscope image of FSi-SiO2. It can be seen from the image that the size of FSi-SiO2 is relatively small.

[0031] Figure 4 This is a scanning electron microscope image of ZrO2 / FSi-SiO2@OMMT. It can be seen that small-sized FSi-SiO2 is attached to OMMT and then combined with large particles composed of medium-sized ZrO2.

[0032] Example 2 The preparation method of the wear-resistant self-cleaning PE film comprises the following steps: 1. The preparation process of wear-resistant self-cleaning agent ZrO2 / FSi-SiO2@OMMT is the same as that in Example 1.

[0033] 2. Mix 3 parts by weight of FSi-SiO2 / ZrO2@OMMT, 0.5 parts by weight of antioxidant 1010, 0.5 parts by weight of antioxidant DLTP, and 1 part by weight of polyethylene wax, and then mix them evenly with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300r / min and a temperature of 60°C, and then place them in a 60°C oven to dry for 1 hour.

[0034] 3. Add the dried raw materials into a twin-screw extruder. The temperature of the first section of the twin-screw extruder is 150°C, the temperature of the second section is 170°C, the temperature of the third section is 165°C, the temperature of the fourth section is 160°C, the temperature of the fifth section is 155°C, and the temperature of the sixth section is 150°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0035] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and then added to the casting machine for extrusion casting, mirror pressing, cooling, trimming, and pressurized winding to obtain a wear-resistant self-cleaning PE film. The casting process is direct casting, the casting roller is a chrome-plated steel roller, the chrome-plated layer thickness is 0.01 mm, the steel roller diameter is 500 mm, and the middle height of the steel roller is 0.20 mm; the steel roller temperature is set to 40°C; the pressurized winding process is pressurized winding on a 60 A liquid silicone rubber roller, and the pressurized pressure is 7Kgf.

[0036] Example 3 The preparation method of the wear-resistant self-cleaning PE film comprises the following steps: 1. The preparation process of wear-resistant self-cleaning agent FSi-SiO2 / ZrO2@OMMT is the same as that in Example 1.

[0037] 2. Mix 4 parts by weight of ZrO2 / FSi-SiO2@OMMT, 0.5 parts by weight of antioxidant 1010, 0.5 parts by weight of antioxidant DLTP and 1 part by weight of polyethylene wax, and then mix them evenly with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, and then place them in a 60°C oven to dry for 1 hour.

[0038] 3. Add the dried raw materials into a twin-screw extruder. The temperature of the first section of the twin-screw extruder is 150°C, the temperature of the second section is 170°C, the temperature of the third section is 165°C, the temperature of the fourth section is 160°C, the temperature of the fifth section is 155°C, and the temperature of the sixth section is 150°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0039] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and then added to the casting machine for extrusion casting, mirror pressing, cooling, trimming, and pressurized winding to obtain a wear-resistant self-cleaning PE film. The casting process is direct casting, the casting roller is a chrome-plated steel roller, the chrome-plated layer thickness is 0.01 mm, the steel roller diameter is 500 mm, and the middle height of the steel roller is 0.20 mm; the steel roller temperature is set to 40°C; the pressurized winding process is pressurized winding on a 60 A liquid silicone rubber roller, and the pressurized pressure is 7Kgf.

[0040] Example 4 The preparation method of the wear-resistant self-cleaning PE film comprises the following steps: 1. The preparation process of wear-resistant self-cleaning agent ZrO2 / FSi-SiO2@OMMT is the same as that in Example 1.

[0041] 2. Mix 5 parts by weight of ZrO2 / FSi-SiO2@OMMT, 0.5 parts by weight of antioxidant 1010, 0.5 parts by weight of antioxidant DLTP and 1 part by weight of polyethylene wax, and then mix them evenly with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, and then place them in a 60°C oven to dry for 1 hour.

[0042] 3. Add the dried raw materials into a twin-screw extruder. The temperature of the first section of the twin-screw extruder is 150°C, the temperature of the second section is 170°C, the temperature of the third section is 165°C, the temperature of the fourth section is 160°C, the temperature of the fifth section is 155°C, and the temperature of the sixth section is 150°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0043] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and then added to the casting machine for extrusion casting, mirror pressing, cooling, trimming, and pressurized winding to obtain a wear-resistant self-cleaning PE film. The casting process is direct casting, the casting roller is a chrome-plated steel roller, the chrome-plated layer thickness is 0.01 mm, the steel roller diameter is 500 mm, and the middle height of the steel roller is 0.20 mm; the steel roller temperature is set to 40°C; the pressurized winding process is pressurized winding on a 60 A liquid silicone rubber roller, and the pressurized pressure is 7Kgf.

[0044] Comparative Example 1 1. Mix 90 parts by weight of LLDPE particles, 0.5 parts by weight of antioxidant 1010, 0.5 parts by weight of antioxidant DLTP and 1 part by weight of polyethylene wax in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, and then place in a 60°C oven to dry for 1 hour.

[0045] 2. Add the dried raw materials into a twin-screw extruder. The temperature of the first section of the twin-screw extruder is 180°C, the temperature of the second section is 175°C, the temperature of the third section is 170°C, the temperature of the fourth section is 165°C, and the temperature of the fifth section is 160°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0046] 3. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and then added to the casting machine for extrusion casting, mirror pressing, cooling, trimming, and pressurized winding to obtain a wear-resistant self-cleaning PE film. The casting process is direct casting, the casting roller is a chrome-plated steel roller, the chrome-plated layer thickness is 0.01 mm, the steel roller diameter is 500 mm, and the middle height of the steel roller is 0.20 mm; the steel roller temperature is set to 40°C; the pressurized winding process is pressurized winding on a 60 A liquid silicone rubber roller, and the pressurized pressure is 7Kgf.

[0047] Comparative Example 2 The preparation method of the wear-resistant self-cleaning PE film comprises the following steps: 1. Specific preparation process of wear-resistant self-cleaning agent ZrO2 / FSi-SiO2@MMT: (1) Add 5 mL of TEOS to a mixed solution of ethanol (50 mL) and ammonia (5 mL, concentration of 28%) and let it stand for 3 h to prepare SiO2 sol. Then add 0.37 g of KH-570 to the SiO2 sol and stir evenly at 60°C for 2 h. Centrifuge the product several times to collect the modified SiO2 particles, and dry them in a drying oven at 50°C for 10 h to obtain FSi-SiO2 with a particle size of 10-100 nm.

[0048] (2) Add 2.30 g FSi-SiO2 and 1.50 g ZrO2 (500-1000 nm) into a three-necked flask containing 20 mL deionized water, adjust the pH to 3 with hydrochloric acid, and stir at 60 °C for 30 min. Then add 2.50 g PFOTES and 7.50 g MMT, and reflux at 60 °C for 13 h. Finally, the mixed solution was dried in an oven at 50 °C and then ground and sieved to obtain powdered ZrO2 / FSi-SiO2@MMT. 2. Mix 4 parts by weight of ZrO2 / FSi-SiO2@MMT, 0.5 parts by weight of antioxidant 1010, 0.5 parts by weight of antioxidant DLTP and 1 part by weight of polyethylene wax, and then mix them evenly with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, and then place them in a 60°C oven to dry for 1 hour.

[0049] 3. Add the dried raw materials into a twin-screw extruder. The temperature of the first section of the twin-screw extruder is 150°C, the temperature of the second section is 170°C, the temperature of the third section is 165°C, the temperature of the fourth section is 160°C, the temperature of the fifth section is 155°C, and the temperature of the sixth section is 150°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0050] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and then added to the casting machine for extrusion casting, mirror pressing, cooling, trimming, and pressurized winding to obtain a wear-resistant self-cleaning PE film. The casting process is direct casting, the casting roller is a chrome-plated steel roller, the chrome-plated layer thickness is 0.01 mm, the steel roller diameter is 500 mm, and the middle height of the steel roller is 0.20 mm; the steel roller temperature is set to 40°C; the pressurized winding process is pressurized winding on a 60 A liquid silicone rubber roller, and the pressurized pressure is 7Kgf.

[0051] Comparative Example 3 The preparation method of the wear-resistant self-cleaning PE film comprises the following steps: 1. Specific preparation process of wear-resistant self-cleaning agent FSi-SiO2@OMMT: (1) 3 g of micron-sized MMT was added to 120 mL of deionized water, stirred at room temperature for 30 minutes, and NaOH solution (0.1 mol / L) was added to adjust the pH of the solution to 12. The mixture was stirred in a water bath at 80 °C for 3 hours under magnetic stirring. 1.9 g of CTAB was dissolved in 50 mL of deionized water and added, and stirring was continued for 3 hours. The final product was centrifuged and washed three times with deionized water and ethanol, and dried at 60 °C for 12 hours to obtain OMMT.

[0052] (2) First, 5 ml of TEOS was added to a mixed solution of ethanol (50 ml) and ammonia (5 ml, concentration of 28%) and allowed to stand for 3 h to prepare SiO2 sol. Then, 0.37 g of KH-570 was added to the SiO2 sol and stirred evenly at 60°C for 2 h. The modified SiO2 particles were collected after multiple centrifugation and dried in a drying oven at 50°C for 10 h to obtain FSi-SiO2 with a particle size of 10-100 nm.

[0053] (3) Add 2.30 g of FSi-SiO2 into a three-necked flask containing 20 mL of deionized water, adjust the pH to 3 with hydrochloric acid, stir at 60 °C for 30 min, then add 2.50 g of PFOTES and 7.50 g of OMMT, and reflux at 60 °C for 13 h. Finally, dry the mixed solution in an oven at 50 °C, grind and sieve to obtain powdered FSi-SiO2@OMMT.

[0054] 2. Mix 4 parts by weight of FSi-SiO2@OMMT, 0.5 parts by weight of antioxidant 1010, 0.5 parts by weight of antioxidant DLTP, and 1 part by weight of polyethylene wax, and then mix them evenly with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, and then place them in a 60°C oven to dry for 1 hour.

[0055] 3. Add the dried raw materials into a twin-screw extruder. The temperature of the first section of the twin-screw extruder is 150°C, the temperature of the second section is 170°C, the temperature of the third section is 165°C, the temperature of the fourth section is 160°C, the temperature of the fifth section is 155°C, and the temperature of the sixth section is 150°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0056] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and then added to the casting machine for extrusion casting, mirror pressing, cooling, trimming, and pressurized winding to obtain a wear-resistant self-cleaning PE film. The casting process is direct casting, the casting roller is a chrome-plated steel roller, the chrome-plated layer thickness is 0.01 mm, the steel roller diameter is 500 mm, and the middle height of the steel roller is 0.20 mm; the steel roller temperature is set to 40°C; the pressurized winding process is pressurized winding on a 60 A liquid silicone rubber roller, and the pressurized pressure is 7Kgf.

[0057] Comparative Example 4 The preparation method of the wear-resistant self-cleaning PE film comprises the following steps: 1. Specific preparation process of wear-resistant self-cleaning agent ZrO2 / FSi-SiO2 and OMMT: (1) 3 g of micron-sized (1-10 μm) MMT was added to 120 mL of deionized water, stirred at room temperature for 30 minutes, and NaOH solution (0.1 mol / L) was added to adjust the pH of the solution to 12. The mixture was stirred in a water bath at 80 °C for 3 hours under magnetic stirring. 1.9 g of CTAB was dissolved in 50 mL of deionized water and added, and stirring was continued for 3 hours. The final product was centrifuged and washed three times with deionized water and ethanol, and dried at 60 °C for 12 hours to obtain OMMT.

[0058] (2) First, 5 mL of TEOS was added to a mixed solution of ethanol (50 mL) and ammonia water (5 mL, concentration of 28%) and allowed to stand for 3 h to prepare SiO2 sol. Then, 0.37 g of KH-570 was added to the SiO2 sol and stirred evenly at 60°C for 2 h. The product was centrifuged several times and collected to obtain the modified SiO2 particles. After drying in a drying oven at 50°C for 10 h, FSi-SiO2 with a particle size of 10-100 nm was obtained.

[0059] 2. Mix 2 parts by weight of ZrO2 / FSi-SiO2, 2 parts by weight of OMMT, 0.5 parts by weight of antioxidant 1010, 0.5 parts by weight of antioxidant DLTP and 1 part by weight of polyethylene wax, and then mix them evenly with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300r / min and a temperature of 60°C, and then place them in a 60°C oven to dry for 1 hour.

[0060] 3. Add the dried raw materials into a twin-screw extruder. The temperature of the first section of the twin-screw extruder is 150°C, the temperature of the second section is 170°C, the temperature of the third section is 165°C, the temperature of the fourth section is 160°C, the temperature of the fifth section is 155°C, and the temperature of the sixth section is 150°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0061] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and then added to the casting machine for extrusion casting, mirror pressing, cooling, trimming, and pressurized winding to obtain a wear-resistant self-cleaning PE film. The casting process is direct casting, the casting roller is a chrome-plated steel roller, the chrome-plated layer thickness is 0.01 mm, the steel roller diameter is 500 mm, and the middle height of the steel roller is 0.20 mm; the steel roller temperature is set to 40°C; the pressurized winding process is pressurized winding on a 60 A liquid silicone rubber roller, and the pressurized pressure is 7Kgf.

[0062] The wear-resistant self-cleaning PE films obtained in Examples 1-4 and Comparative Examples 1-4 were subjected to mechanical tests, and the test results are shown in Table 1.

[0063] Table 1 Mechanical properties test results Table 1 is the mechanical property test results of each embodiment and each comparative example. It can be clearly seen from the above performance test results that, in embodiments 1-4, as the amount of wear-resistant self-cleaning filler added increases, the tensile strength of the PE film shows a trend of first rising and then slightly decreasing, while the longitudinal elongation at break and the transverse right-angle tear strength have been rising, indicating that the mechanical properties of the PE film are improved with the addition of fillers. When the amount of wear-resistant self-cleaning agent added reaches 5 parts (Example 4), the tensile strength decreases slightly, while the transverse elongation and the longitudinal right-angle tear strength also decrease compared to Example 3. It may be that the wear-resistant self-cleaning agent is added too much, and it agglomerates in the matrix material, resulting in reduced mechanical properties. According to comparative examples 1-4, the PE film is less improved after the addition of fillers that have not been organically modified, and the elongation is even reduced. Although the performance is also improved when the nanomaterial is not loaded, it is not as good as the improvement after loading. The reason is also that the unloaded nanomaterial agglomerates, which limits the performance improvement.

[0064] Table 2 Wear resistance and self-cleaning properties of the films The data in Table 2 show that the addition of wear-resistant self-cleaning agent ZrO2 / FSi-SiO2@OMMT significantly improves the wear resistance and self-cleaning properties of the film. In Examples 1-4, as the amount of wear-resistant self-cleaning filler added increases, the wear resistance of the film has been improving, while its self-cleaning performance first increases and then decreases. The continuous improvement in wear resistance is due to the addition of modified ZrO2, and the reason for the decrease in self-cleaning performance after the increase is the same as the mechanical properties, and the performance of the agglomerated material has not been fully utilized. By comparing Example 3 with Comparative Example 2, it can be seen that the compatibility of unmodified MMT in the resin material is worse than that of OMMT, which also affects the performance of the polyethylene film. By comparing Example 3 with Comparative Example 4, it can be seen that using ZrO2 / FSi-SiO2@OMMT as an antibacterial and antifouling agent, compared with the separate addition of ZrO2 / FSi-SiO2+OMMT, loading on OMMT can improve the compatibility and dispersibility of ZrO2 / FSi-SiO2 with the matrix resin to a certain extent, thereby improving the wear resistance and self-cleaning properties of the polyethylene film. Comparison between Example 3 and Comparative Example 3 also shows that the addition of ZrO2 improves the wear resistance of the polyethylene film.

[0065] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A wear-resistant self-cleaning polyethylene film, characterized in that: The polyethylene film comprises the following raw materials by weight: LLDPE 90 parts; 2-5 parts of wear-resistant self-cleaning agent; Antioxidant 1010 0.5-1 part; 1-3 parts of polyethylene wax; Antioxidant DLTP 0.5-1 part; The wear-resistant self-cleaning agent is ZrO2 / FSi-SiO2@OMMT.

2. The wear-resistant self-cleaning polyethylene film according to claim 1, characterized in that: The preparation method of the wear-resistant self-cleaning agent ZrO2 / FSi-SiO2 @OMMT comprises the following steps: (1) Preparation of OMMT: 3 g of micron-sized montmorillonite was added to 120 mL of deionized water, stirred at room temperature for 30 minutes, 0.1 mol / L NaOH solution was added to adjust the pH of the solution to 12, and stirring was continued at 80 °C for 3 hours; 1.9 g of hexadecyltrimethylammonium bromide was dissolved in 50 mL of deionized water and added to the above solution and stirring was continued for 3 hours. After the reaction was completed, OMMT was obtained by centrifugation, washing, and drying; (2) Preparation of FSi-SiO2: First, add 5 mL of tetraethyl orthosilicate to a mixed solution of ethanol and ammonia water, and let it stand for 3 h to obtain SiO2 sol; add 0.37 g of KH-570 to the SiO2 sol, stir evenly at 60 °C for 2 h, centrifuge after the reaction is completed, and dry to obtain FSi-SiO2; (3) Preparation of ZrO2 / FSi-SiO2@OMMT: Add 2.30 g FSi-SiO2 and 1.50 g ZrO2 into 20 mL deionized water, adjust the pH of the solution to 3 with hydrochloric acid, and stir at 60 °C for 30 min. Then add 2.50 g perfluorooctyltriethoxysilane and 7.50 g OMMT, and reflux at 60 °C for 13 h. After the reaction, the resulting solution was dried at 50 °C and then ground and sieved to obtain powdered ZrO2 / FSi-SiO2@OMMT.

3. The polyethylene film according to claim 2, characterized in that: The volume ratio of ethanol to ammonia water in step (2) is 10:

1.

4. A method for preparing the wear-resistant self-cleaning polyethylene film as claimed in claim 1, characterized in that: The following steps are involved: (1) After the wear-resistant self-cleaning agent, antioxidant 1010, antioxidant DLTP and polyethylene wax are mixed evenly, they are added into a high-speed mixer and mixed evenly with LLDPE particles, and then dried at 60°C for 1 hour; (2) Adding the dried material into a twin-screw extruder and obtaining masterbatch by extrusion granulation; (3) The obtained masterbatch is dried and then added to a casting machine for extrusion casting, mirror pressing, cooling, trimming, and pressurized winding to obtain a wear-resistant self-cleaning PE film.

5. The preparation method according to claim 4, characterized in that: The speed of the high-speed stirrer in step (1) is 300 r / min and the temperature is 60°C.

6. The preparation method according to claim 4, characterized in that: The extrusion temperatures of the twin-screw extruder used in step (2) are: 150°C in the first section, 170°C in the second section, 165°C in the third section, 160°C in the fourth section, 155°C in the fifth section, and 150°C in the sixth section; the screw speed is 10 r / min.

7. The preparation method according to claim 4, characterized in that: The casting process used in step (3) is direct casting, the casting roller is a chrome-plated steel roller, the thickness of the chrome-plated layer is 0.01 ~ 0.015mm, the diameter of the steel roller is 500mm, and the middle height of the steel roller is 0.20 ~ 0.25mm; the temperature of the steel roller is set to 35 ~ 40°C; the pressurized winding process is pressurized winding on a 6065A liquid silicone rubber roller, and the pressurized pressure is 5 ~ 8Kgf.

Citation Information

Patent Citations

  • Core-shell type catalyst for directional catalytic conversion of biomass synthesis gas, and preparation of core-shell type catalyst

    CN108906070A

  • High-strength composite PE diaphragm and preparation method thereof

    CN110797495A

  • Wear-resistant polyethylene film material

    CN111440376A

  • High barrier RGO-sio2 / pet protective film and preparation method therefor

    WO2021128808A1

  • IDP000513061A